Using Patient- and Family-Reported Outcome and Experience Measures Across Transitions of Care for Frail Older Adults Living at Home: A Meta-Narrative Synthesis. (16th January 2020) - Schick-Makaroff, Kara; Karimi-Dehkordi, Mehri; Cuthbertson, Lena; Dixon, Duncan; Cohen, S Robin; Hilliard, Neil; Sawatzky, Richard
Abstract: Background and Objectives: Our aim was to create a "storyline" that provides empirical explanation of stakeholders' perspectives underlying the use of patient- and family-reported outcome and experience measures to inform continuity across transitions in care for frail older adults and their family caregivers living at home. Research Design and Methods: We conducted a meta-narrative synthesis to explore stakeholder perspectives pertaining to use of patient-reported outcome and experience measures (PROMs and PREMs) across micro (patients, family caregivers, and healthcare providers), meso (organizational managers/executives/programs), and macro (decision-/policy-makers) levels in healthcare. Systematic searches identified 9, 942 citations of which 40 were included based on full-text screening. Results: PROMs and PREMS (54 PROMs; 4 PREMs; 1 with PROM and PREM elements; 6 unspecified PROMs) were rarely used to inform continuity across transitions of care and were typically used independently, rarely together ( n = 3). Two overarching traditions motivated stakeholders' use. The first significant motivation by diverse stakeholders to use PROMs and PREMs was the desire to restore/support independence and care at home, predominantly at a micro-level. The second motivation to using PROMs and PREMs was to evaluate health services, including cost-effectiveness of programs and hospital discharge (planning); this focus was rarely at a macro-level and more often split between micro- and meso-levels of healthcare. Discussion and Implications: The motivations underlying stakeholders' use of these tools were distinct, yet synergistic between the goals of person/family-centered care and healthcare system-level goals aimed at efficient use of health services. There is a missed opportunity here for PROMs and PREMs to be used together to inform continuity across transitions of care.